Depression and Anxiety Across the First Year After Ischemic Stroke: Findings from a Population-Based New Zealand ARCOS-IV Study. Issue 3 (29th June 2017) - Barker-Collo, Suzanne; Krishnamurthi, Rita; Witt, Emma; Theadom, Alice; Starkey, Nicola; Barber, P. Alan; Bennett, Derrick; Rush, Elaine; Arroll, Bruce; Feigin, Valery
Abstract : Background: Depression and anxiety are the two most frequently studied emotional outcomes of stroke. However, few previous studies have been carried out at a population level or beyond 6 months post stroke. The aim of this study was to describe depression and anxiety across the first year following incident ischemic stroke (IS), and identify predictive factors in a population-based study. Method: The Hospital Anxiety Depression Scale (HADS) was administered at baseline (within 2 weeks of onset), and again at 1-month, 6-months and 12-months after IS in a sample ( N = 365) drawn from a population-based study. Results: Over 75% of those assessed experienced depression or anxiety symptoms below cut-offs for probable disorder across the year post stroke. Moderate to severe symptoms for anxiety were approximately twice as likely (range 4.1%–10.6%) as compared to depression (range 2.5%–5.0%) at each assessment. The greatest improvement in anxiety occurred within the first month post stroke. In contrast, the greatest reduction in depression occurred between 1- to 6-months post stroke. Conclusions: Anxiety symptoms in the moderate to severe range were twice as common as depression, and improved over the first month post stroke, whilst depression symptoms persisted for up to 6 months, indicating a need to target these two issues at different points in the recovery process.